2013
DOI: 10.1007/s00404-013-2930-9
|View full text |Cite
|
Sign up to set email alerts
|

Modified LeFort colpocleisis: clinical outcome and patient satisfaction

Abstract: The study highlights an additional safe and effective option for an individualized treatment of pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 7 publications
2
16
0
4
Order By: Relevance
“…Out of the remaining 38 articles only 23 were based on studies focusing on colpocleisis or colpectomy and related surgical techniques or outcome measures. Some reports focused on clinical outcomes following partial Neugebauer-Le Fort colpocleisis, total colpocleisis or partial colpectomy [1][2][3][4][5][6][7][8][9][10]. These papers dealt mainly with objective or subjective cure rates after prolapse surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the remaining 38 articles only 23 were based on studies focusing on colpocleisis or colpectomy and related surgical techniques or outcome measures. Some reports focused on clinical outcomes following partial Neugebauer-Le Fort colpocleisis, total colpocleisis or partial colpectomy [1][2][3][4][5][6][7][8][9][10]. These papers dealt mainly with objective or subjective cure rates after prolapse surgery.…”
Section: Resultsmentioning
confidence: 99%
“…To our understanding, while the first refers to a full oncologic excision of all vaginal and paravaginal tissues down to the vulva, the latter refers to a removal of the vaginal skin with surgical closure of the limbs of the levator ani muscle for prolapse surgery. So far, all reports focused on surgical techniques preserving the integrity of the suburethral tissue (usually the first 3cm of the anterior vaginal wall), even when total colpectomy was performed for pelvic organ prolapse [4,5,11,12]. Some authors reported on combined prolapse and incontinence surgery, where up to 100% of their patients underwent concomitant midurethral sling placement at time of colpocleisis [1,9,13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Al igual que en otros estudios, como el realizado en la serie de Zhu 9 y Reisnauer et al 4 , en el nuestro tambien se demostro un alta tasa de satisfacción, demostrada en el no arrepentimiento de la intervención y consecuentemente de la perdida de la función sexual.…”
Section: Discussionunclassified
“…La tasa de curación de nuestros hallazgos es similar a la informada por Reisenauer et al 4 y Zebede et al 8 Sin embargo en nuestro grupo de estudio, la mayoria de las pacientes (97.9%) evaluadas tenian comorbilidades, repecto a otros estudios evaluados, que aunque tuvieron resultados similares, tenian menor porcentaje de comorbilidades como en el de Zebede et el 8 .…”
Section: Discussionunclassified
See 1 more Smart Citation